2013
DOI: 10.1002/hbm.22228
|View full text |Cite
|
Sign up to set email alerts
|

Mapping white matter integrity in elderly people with HIV

Abstract: People with HIV are living longer as combination antiretroviral therapy (cART) becomes more widely available. However, even when plasma viral load is reduced to untraceable levels, chronic HIV infection is associated with neurological deficits and brain atrophy beyond that of normal aging. HIV is often marked by cortical and subcortical atrophy, but the integrity of the brain’s white matter (WM) pathways also progressively declines. Few studies focus on older cohorts where normal aging may be compounded with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 110 publications
(150 reference statements)
12
56
1
Order By: Relevance
“…2) The frontal lobe white matter and CSO may be subject to early injury in patients infected with HIV, and this agrees with previous HIV studies [3,5,10,22,24,25]. Smith AB et al [25] reported that there is a frontal lobe white matter predominant involvement in HIV infection of the brain.…”
Section: Rois Groupssupporting
confidence: 75%
See 1 more Smart Citation
“…2) The frontal lobe white matter and CSO may be subject to early injury in patients infected with HIV, and this agrees with previous HIV studies [3,5,10,22,24,25]. Smith AB et al [25] reported that there is a frontal lobe white matter predominant involvement in HIV infection of the brain.…”
Section: Rois Groupssupporting
confidence: 75%
“…Otherwise, Stubbe-Drger B et al [3,5,10] suggested that FA could be more sensitive than other MRI approaches to microstructural white matter abnormalities. This may be due to the differences in patients receiving HAART or not, in our study, all patients were not receiving any antiretroviral treatment, their participants were on a stable antiretroviral regimen for at least 12 consecutive weeks prior to study, based on this inconsistency, we will continue to study the effects of HAART on white matter DTI parameters of HIV patients.…”
Section: Rois Groupsmentioning
confidence: 95%
“…The findings that FA values within the genu, body, and splenium of the corpus callosum were reduced in HIV-positive adolescents are consistent with findings in previous studies on HIV-infected children and adults. For example, FA values for the genu, 10 body, 21 and splenium 8 of the corpus callosum 11,22 are significantly reduced in HIV-infected adults. Decreased FA of the body of corpus callosum is also reported in HIV-infected children.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, deceased FA is also found in the anterior and superior corona radiata in HIV-infected participants. 10,11 The anterior corona radiata is associated with functions of the executive network. 26 Previous studies have focused on HIV-infected children and found that the subjects displayed visual-spatial memory and motor developmental deficits and executive function disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation